Anatomical study of superficial fascia and localized fat deposits of abdomen - Pramod Kumar; Arvind K Pandey; Brijesh Kumar; Shrinivas K Aithal (Indian Journal of Plastic Surgery)
Background: The development of liposuction and abdominoplasty has renewed interest in the anatomy of the localized fat deposits (LFD) areas of the abdomen. This study aims at ascertaining the gross anatomy of superficial fascia and the localized fat deposits of abdomen. Materials and Methods: Eight adult cadavers (four males and four females) were dissected. Attachments, number of layers of fascia and colour, shape and maximum size of the fat lobules in loin, and upper and lower abdomen were noted. Thickness of deep membranous layer of superficial fascia of upper abdomen and lower abdomen were measured by metal casing electronic digital calipers, with resolution being 10 μm. The independent sample t-test, ANOVA for comparison and Pearson coefficient for correlation were used. Results: Superficial fascia of the abdomen was multilayered in the midline and number of layers reduced laterally. The shape, size, color, and arrangement of fat lobules were different in different locations. The thickness of the fascia of the lower abdomen in males (mean 528.336 ± SE38.48) was significantly (P < 0.041) more than that in females. (Mean 390.822 ± SE36.24). Pearson correlation between thickness of the membranous layer of the upper and lower abdomen revealed moderately positive correlation (r=0.718; P<0.045). Conclusions: The LFD in the central region of the abdomen corresponds to the area of multilayered fascia with smaller fat lobules. The relatively thinner supporting fascia of the lower abdomen in females may be responsible for excessive bulges of the lower abdomen. The fat lobule anatomy at different sites under study was different.